Satisfaction With a Virtual Learning Collaborative Aimed at Implementing Treat-to-Target in Rheumatoid Arthritis. Issue 5 (24th August 2022) - Ellrodt, Jack; Pincus, Theodore; Shadick, Nancy A.; Stratton, Jacklyn; Santacroce, Leah; Katz, Jeffrey N.; Smolen, Josef; Solomon, Daniel H.
Abstract : Objective: Limited information is available concerning experiences of participants in a virtual learning collaborative (LC), and little qualitative data or participant feedback on how this format can be improved. One prior in-person LC in rheumatology successfully improved adherence with treat-to-target (TTT) for RA. We conducted a virtual LC on TTT and herein report on participant satisfaction. Methods: We conducted a virtual LC with 18 rheumatology practices from across the United States during 2020 to 2021. The LC included a virtual kickoff meeting and monthly videoconferences, accompanied by data submission and feedback. At the conclusion of the LC, we surveyed the 45 LC participants concerning individual experience and satisfaction. Results: All sites and 78% of participants responded to the surveys. The LC included small and large practices, 14 academic and 4 nonacademic, and respondents ranged in their roles: 24 physicians, 5 nurses or nurse practitioners, 3 administrators, and 3 other roles. Overall, 94% of respondents indicated they were either somewhat or very satisfied with the LC, and 94% said they would recommend a similar LC to a colleague. Aspects of the LC described as "very useful" included a kickoff meeting, intersite discussion, and monthly speakers; however, digital tools such as the Web site and meeting recordings were not found useful. Conclusions: Virtual LCs are feasible, and participants reported strong satisfaction. Virtual LCs were highly valued by rheumatologists, trainees, and their practice staffs. Potential topics were identified for future LCs that could improve the quality of care delivered to rheumatology patients.